2015
DOI: 10.1039/c4ra17164k
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanocluster-enhanced peroxynitrous acid chemiluminescence for high selectivity sensing of nitrite

Abstract: Peroxynitrous acid (ONOOH) produced by online mixing of nitrite and acidified hydrogen peroxide could induce weak chemiluminescence (CL). A stronger chemiluminescence was observed in the presence of gold nanoclusters (Au NCs). This novel CL system was developed as a flow-injection method for the nitrite determination directly and conveniently. This method was achieved in acidic medium, which greatly improved its selectivity. The CL mechanism of the peroxynitrous acid-gold nanocluster system was investigated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…BSA has been used frequently since Ying et al [77] developed a new method for preparing Au NCs with red emissions using BSA to sequester and reduce Au precursors in situ. Many scientists found BSA@AuNCs [46,[78][79][80], BSA@Cu NCs [81,82], and BSA@Zn/Cu alloy NCs [83] could act as ECL emitter or CL catalyst to enhance ECL or CL signal. Graphene/multiwall carbon nanotube hybrid (GP/MWCNTs) could be also used as template to prepare GP/MWCNTs/Au NCs composite [84].…”
Section: Template-assisted Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…BSA has been used frequently since Ying et al [77] developed a new method for preparing Au NCs with red emissions using BSA to sequester and reduce Au precursors in situ. Many scientists found BSA@AuNCs [46,[78][79][80], BSA@Cu NCs [81,82], and BSA@Zn/Cu alloy NCs [83] could act as ECL emitter or CL catalyst to enhance ECL or CL signal. Graphene/multiwall carbon nanotube hybrid (GP/MWCNTs) could be also used as template to prepare GP/MWCNTs/Au NCs composite [84].…”
Section: Template-assisted Synthesismentioning
confidence: 99%
“…In 2005, Au nanoparticles-amplified luminol CL was reported by Cui et al [86]. Since then, a series of different CL systems based on Au, Ag, Pt, ZnO nanoparticles has been investigated [87][88][89][90] and it was found that some metal NCs (e.g., Au, Ag, Cu, Zn/Cu alloy NCs ) could enhance intensity of CL systems including luminol-H 2 O 2 [81,91], luminol-KMnO 4 [82], NaNO 2 -H 2 O 2 [78], Ce(IV)-Na 2 SO 3 [70,71], NaHCO 3 -H 2 O 2 [83].…”
Section: Chemiluminescence Applications Of Metal Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental conditions: SCNions was 0.3 µM, other ions were 0.03 mM, Na2C2O4 was 1.2 mM.Analytical SciencesAdvance Publication by J-STAGE Received December 17, 2019; Accepted February 14, 2020; Published online on February 28, 2020 DOI: 10.2116/analsci.19P475Fig. 7(a) When SCNin different concentrations (0,5,10,15,20,25,30, 60, 90, 120, 150, 180 nM) existed in Au@Pt NPs-luminuol-H2O2 system, CL kinetic curves of SCNwere detected.The black curve was the CL kinetic curve for the reaction of luminol + H2O2, (b) Calibration curve of SCN -. Experimental conditions: luminol and H2O2 reaction time was 4 h, 3.5 mM luminol in 0.1 M NaOH solution, Au@Pt NPs was 0.3 nM, H2O2 was 10 mM.…”
mentioning
confidence: 99%
“…6 Consequently, rapid and sensitive determination of nitrite levels is essential for monitoring human health in many aspects, such as in drinking water and daily foods, as well as clinical diagnosis. 7,8 To this end, many analytical methods have been developed for the detection of nitrite, such as spectrophotometry, [9][10][11][12] electrochemical analysis, [13][14][15][16][17][18] chemiluminescence, 19,20 etc. However, these traditional methods oen require complicated and expensive instruments, and may cause the secondary pollution due to the use of high toxicity diazo coupling reagent.…”
mentioning
confidence: 99%